Multimodality imaging features of systemic amyloidosis: a case report - Yi Yu; Zhi-Chao Li; Guang-Yin Li; Ting Wang; Yi-Gang Li (BMC Cardiovascular Disorders)
Abstract Background Systemic light chain amyloidosis is a rare and debilitating disease, especially for which initially presented with digestive tract involvement. Myocardial amyloidosis is highly aggressive with generally poor prognosis and often resulted in missed diagnosis or misdiagnosis with routine examination tools. Multimodality imaging play an important role in diagnosing the amyloidosis effect on multiple organs. Chemoradiotherapy is the mainstay of treatment. Case presentation This article presents a rare case of systemic light chain amyloidosis, initially with gastrointestinal symptoms, in a 68-year-old male. He was hospitalized with diarrhea for one year and a half, dysphagia for 4 months, but he had no dyspnea. The transthoracic echocardiogram revealed myocardial hypertrophy of the left ventricle, the hypertrophic heart muscle echoed like "ground glass". The left ventricular ejection fraction (LVEF) detected by Simpson method was 51% and global longitudinal strain (GLS) was -9.00%. But cardiac magnetic resonance showed the patient without gadolinium delayed enhancement. The urinary protein series quantification and the serum free light chain levels were all increased. While the ratio of free κ and free λ was decreased. Hence, the abdominal fat biopsy of the patient was amyloidosis by electronic and immunoelectron microscopy. Organs involved include heart, kidneys, gastrointestinal tract and nervous system, stage III of mayo 2012 model. The patient was treated with Dara-BCD chemotherapy. This case underscores the diagnostic complexity, emphasizing the need for early identification given the grim prognosis associated with systemic AL amyloidosis requiring clinical data, detailed imaging, and histopathological insights. After discharge, the patient became better and followed up in the outpatient. Conclusions Systemic light chain amyloidosis can easily be missed diagnosis or misdiagnosis in its early stages, losing the opportunity for initiating earlier treatments to improve potential patient outcomes. Despite advancements in diagnostic biomarkers, this case highlights the potential for missed diagnosis with standard CMR imaging when gadolinium enhancement is negative. The utility of echocardiographic features such as reduced GLS and abnormal ECG findings emerges as critical in early identification of myocardial amyloidosis. The correct diagnosis of this case relied on the comprehensive utilization of multimodal imaging techniques including biopsy.